A Unified Analysis of Particle Capture by Air Bubble - P. T. Nguyen (International Mineral Processing Congress, 2014)
The analysis of particle capture by an air bubble by two separate phenomena of collision and attachment has been difficult due to the uncertainty in determining when and where the two phenomena begin and terminate at the bubble surface, respectively. Therefore, a unified analysis was developed by solving the motion equation for the particle capture as one process. No distinction be-tween collision and attachment was made. Both the liquid film described by the micro-hydrodynamic resistance functions and the surface forces were included in the new model. The model predictions with the DLVO (Derjaguin-Landau-Verwey-Overbeek) surface forces did not agree with the experimental trajectories of latex and silica spheres. The model predictions with the inclusion of the non-DLVO attractive surface force agreed with the experimental data. The non-DLVO force reduced the repulsion between the non-attaching particle and the bubble, and significantly increased the attraction between the attaching particle and the bubble. The unified analysis is capable of predicting particle capture without the use of the induction time. The unified analysis also shows significant influence of the short-range hydrodynamic interactions on the collision which has been previously ignored.